Analisis Yuridis Pemberian Dispensasi Nikah dengan Alasan Sudah Tinggal Bersama ditinjau dari Hukum Islam, UU Perkawinan dan UU Perlindungan Anak : (Studi Putusan PA Larantuka/83/PDT.P/PA. LRT) - Nur`aini Jihan Wijayanti (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Marriage dispensation is a granting of marriage permit by the court to prospective husband and wife who are not yet 19 years old to get married. The granting of this permit has a significant impact on the rampant child marriage. Moreover, the author found a decision granting marriage dispensation on the grounds of having lived together for five months as stated in the Decision of the Larantuka PA/83/PDT.P/PA. LRT. From this background, the author is interested in finding out whether the granting of marriage dispensation on the grounds is in accordance with Islamic Law, the Marriage Law and the Child Protection Law or not. This study was conducted using a qualitative juridical method by examining library materials. The results of the study indicate that the granting of marriage dispensation on the grounds has not met the provisions of Islamic Law, the Marriage Law and the Child Protection Law. This is because there is still a lack of sufficient evidence to accept the application for marriage dispensation in the form of a health certificate and a mental age test to determine the health, both physically and mentally, of the child. Thus, the decision does not reflect the best interests of the child in the form of the right to health insurance for children.